Composición, diversidad y abundancia de peces en el embalse Arenal, Guanacaste, Costa Rica - Ulloa Rojas, Juan B. (1989)
The abundance, species diversity. richneiS, dominance, evenness and similarity índices of the fish cornmunities at two stations in the Arenal Reservoir, Guanacaste, Costa Rica, were estimated between April 1984 and April 1985. Melaniris chagresi and Poecilia gillii were the most abundant species, with 86.93 %and 6.11% of total captured fishes (15,941). The Shannon-weaver diversity index was 0.32 for the Sangregado station and 0.31 for the Campamento station. There were not significant differences in indices between the two stations.